PEMBERDAYAAN PEREMPUAN KEPALA KELUARGA (PEKKA) TUNON TERHADAP RESILIENSI PEREMPUAN DI KABUPATEN GIANYAR - Sri Astuti, Ni Nyoman; Wismayanti, Kadek Wiwin Dwi; Wirantari, I Dewa Ayu Putri (CITIZEN CHARTER, 2024)
The empowerment of the female head of the family (Pekka) Tunon is an effort to improve the ability and potential of the female head of the family to actualize themselves, dignity to the maximum in order to survive and be independent in Banjar Tunon, Singakerta Village, Gianyar Regency. This research aims to find out the extent of empowerment carried out by the Pekka Tunon Group and the extent to which the resilience owned by Pekka members receives empowerment. Research methods use qualitative descriptive with data collection techniques in the form of observations, interviews, and documentation. It was found that in Pekka Tunon went through four stages of the empowerment process according to Wilson including awakening, understanding, Harnessing, and using. Pekka members also have good resilience while participating in empowerment because community support can be found from persistence, strength, and optimism as the female head of the family. Keywords: Empowerment, Female Head of The Family, Pekka Program, Resilience